2009
DOI: 10.1038/ng.382
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in LIN28B is associated with the timing of puberty

Abstract: The timing of puberty is highly variable1. We carried out a genome-wide association study for age at menarche in 4,714 women and report an association in LIN28B on chromosome 6 (rs314276, minor allele frequency (MAF) = 0.33, P = 1.5 × 10 −8 ). In independent replication studies in 16,373 women, each major allele was associated with 0.12 years earlier menarche (95% CI = 0.08-0.16; P = 2.8 × 10 −10 ; combined P = 3.6 × 10 −16 ). This allele was also associated with earlier breast development in girls (P = 0.001;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
294
4
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(311 citation statements)
references
References 14 publications
8
294
4
5
Order By: Relevance
“…This approach is limited for a complex phenotype because it implicates only very few genes. Previous studies used this approach to report associations of the genes CCR3, SPOCK1, LIN28B, ZNF462, TMEM38B, FKTN, FSD1L, and TAL2 with age of puberty in women (11)(12)(13)(14)(15). If we applied only this approach to our data, further research would consider one candidate gene, NMDAR2B, which was strongly associated (P < 0.000015) with AGECL.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is limited for a complex phenotype because it implicates only very few genes. Previous studies used this approach to report associations of the genes CCR3, SPOCK1, LIN28B, ZNF462, TMEM38B, FKTN, FSD1L, and TAL2 with age of puberty in women (11)(12)(13)(14)(15). If we applied only this approach to our data, further research would consider one candidate gene, NMDAR2B, which was strongly associated (P < 0.000015) with AGECL.…”
Section: Discussionmentioning
confidence: 99%
“…While one initial study reported an association with the SPOCK locus that has not been replicated (77), four independent papers published in May 2009 identified an association of the age at menarche (AAM) with variability at 6q21, in or near the Lin28B gene (78,79,80,81). The robustness of this finding is reinforced by its recent confirmation in an extensive meta-analysis (82), and the fact that Lin28B had also been linked to breast development and adult height.…”
Section: Role Of Nesfatin-1 In Puberty Onset: Supporting Evidencementioning
confidence: 99%
“…In turn, let7 miRNAs participate in the regulation of Lin28B expression, which is also putatively controlled by other miRNAs, such as mir-132 and mir-145 (as predicted by bioinformatic algorithms), and myc itself. Before the GWAS indicated earlier (78,79,80,81), the potential roles of let7 miRNAs and related factors in the control of puberty or other neuroendocrine functions had not been suspected. On the contrary, let7 miRNAs were initially cataloged as putative tumor suppressors (88).…”
Section: Role Of Nesfatin-1 In Puberty Onset: Supporting Evidencementioning
confidence: 99%
“…The age at menarche and menopause influences the risk of several diseases; for example, the earlier age of menarche and/or later age of menopause increases the risk of breast, ovarian and endometrial cancers. Three studies focused on the age at menarche, [96][97][98] one GWAS studied the age at natural menopause, 99 and the other GWAS investigated both the traits. 100 Several loci were identified for menarche, but all the four studies definitely found an association in the 6p21 locus that contained LIN28B (a height-related gene) and two GWAS detected another locus 9q31.2.…”
Section: The Recent 2 Years: 2008 and 2009mentioning
confidence: 99%